Overview of Hemoglobin Level in Teenage Girls after Fe Tablet Supplementation in Batam - Susanti; Ulpawati (HM Publisher, 2022)
Many factors can cause iron deficiency anemia with iron loss during menstruation, especially in teenagers. This study was aimed to describe hemoglobin levels related to Fe supplementation in teenage girls in Batam. This study is descriptive and observational research. The research was conducted at SMAN 5 Batam from May to July 2021. The inclusion criteria for the participant in this study were girls aged 14 to 17 years old, willing to participate in this study, and signed the informed consent. A total of 47 girls participated in this study. Hemoglobin level was recorded before and after supplementation. Most of the participants were over 15 years old (91.5%) and had normal menstrual cycles. All participants had menstruated and had no history of infectious disease. The results of the Hb level examination showed that before the administration of Fe tablets, 95.7% of the participants had normal Hb levels. However, after Fe supplementation, the number of participants who had normal Hb levels decreased to 87.2% of the total participants who took part in this study. In conclusion, we found a decrease in the number of participants who had normal Hb levels after Fe supplementation.